Global Structure of Positive Solutions of a Discrete Problem with Sign-Changing Weight - Ruyun Ma; Chenghua Gao; Xiaoling Han; Xiaoqiang Chen (Discrete Dynamics in Nature and Society)
Let T>5 be an integer, T={1,2,…,T}. We are concerned with the global structure of positive solutions set of the discrete second-order boundary value problems Δ2u(t-1)+rm(t)f(u(t))=0,  t∈T,  u(0)=u(T+1)=0, where r∈ℝ is a parameter, m:T→ℝ changes its sign and m(t)≠0 for  t∈T.